Analisis Penawaran Ekspor Minyak Bumi Mentah Indonesia Pada Pasar Global Tahun 2009-2018 - Fahrizal Yazid; Aris Soelistyo; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2020)
The research objective is to determine the effect of the exchange rate, domestic and global inflation, GDP of each country, the export of crude oil in the previous year on Indonesia's crude oil exports. The number of samples used was 7 countries with a purposive sampling method. The method used is a quantitative method using secondary data obtained from the World Bank, Central Statistics Agency, Bank Indonesia. The analytical tool used is panel data regression. The results of this study indicate that the exchange rate, domestic inflation, crude oil exports in the previous year had a significant positive effect on Indonesia's crude oil exports and inflation to the destination country had a significant negative effect on Indonesia's crude oil exports, while the GDP did not have a significant positive effect on exports Indonesian crude oil.